Biosorption of chromium by dry algae Chlorella kessleri. Issue 1 (November 2021) - Takáčová, A; Bajuszová, M; Kohanová, J; Lux, A; Valent, P; Kokavcová, A; Takáčová, L
Abstract: Decontamination of environment according to traditional methods is not only economically inaccessible but also often highly environmentally harmful. It is necessary to apply methods that are environmentally friendly as possible. These methods include bioremediation, which uses organisms able to fight with high concentrations of pollutants to decontaminate the environment. In this study, we observed the biosorption of chromium from the aquatic environment using dried algae Chlorella kessleri . The results of the specific sorption at pH = 4.00 in the chromium model sample had a value of q = 5.9 mg / g, which represented a decrease in the chromium concentration by 74%. The specific sorption in the case of the native chromium sample q after 24 hours reached the highest value (q = 2.74 mg / g) at pH = 4.00. During the experiment, we observed a constant change in the content of photosynthetic pigments in the prepared solutions where it was shown that after 24 h exposure the yield of chlorophyll a was decrease by 95.91% compare to control. In the case of chlorophyll b, the same trend was demonstrated where 91.92% decrease of its content after 24 hours was observed. This type of dried alga has been shown to be a rapid biosorbent, in relatively short time intervals. The results of the study show that in the process of decontamination there was not only the binding of chromium to the cell surface but also its penetration through the cell wall.